Comparative Study on Different Methods for Seismic Safety Evaluation of Existing Multi-Storied Reinforced Concrete Buildings: Comparative Analysis of Seismic Evaluation Methods for Existing Multi-Storied Buildings (Journal of Advances and Scholarly Researches in Allied Education, 2016)
A research work is to propose a method for seismic safety evaluation of existing multi-storied reinforced concrete buildings It is expected that buildings designed based on the code provisions should be able to with stand minor earthquakes without detriment, resistor-structural damage and resist major earthquakes without moderate earthquakes with some Collapse, but with some structural as well as non-structural damage. Seismic provisions in the building codes have advance over the years to achieve this goal. Many parts of our country in there subjected to major earthquakes of magnitude greater than or equal to 8 (on Richter’s past scale). Moderate earthquakes have also caused severe damage in many places. The need for evaluation arises mainly due to two causes first, most of the existing RC buildings, particularly the old ones, have not been designed to resist earthquake forces due to lack of awareness Secondly, due to the revision of the existing seismic codes, Even buildings designed by previous codes for seismic forces can become unsafe because of the increase in the seismic forces proposed. In India, because of the revision of IS 1893-1984 in 2002, we are facing this situation. Our town in Hyderabad is now under seismic zone II, while it used to be in zone I. Hence, it is necessary to evaluate the seismic safety of all buildings in general and multi-strayed building sin particular as they are liable to suffer more damage. Unsafe buildings can be strengthened to that resist the future earthquakes safely.to develop a Simplified Seismic Evaluation Method for the assessment of the existing RC buildings for seismic vulnerability. Compare A Results obtained from the proposed method with the results obtained from FEMA -154, FEMAP-155 and New Zealand.